Uji Performansi Prototipe Alat Pengering Kopra Memanfaatkan Panas Buang PLTU Berbahan Bakar Arang Tempurung Kelapa - Dedi Suntoro; Subhan Nafis; Hablinur Al-Kindi (PERTETA, 2018)
AbstractThe exhaust heat of steam power plant has considerable energy potential that can be recovered for various processes, one of which is for the drying of materials. The purpose of this research is to know the performance of a copra dryer by utilizing exhaust heat from coconut shell charcoal fired power plant which has been developed by P3TKEBTKE. Copra dyers consisting of a fan, heat exchangers, and a drying chamber are installed on the boiler combustion flue gas duct as the heat source. This research was conducted by varying fan speed at 2.2 m/s and 3.7 m/s. The results show the drying room temperature between 36-130°C, are not equally distributed. The test results with the air flow rate of 4.14 m3/m shows the average temperature of 72.18°C drying copra final moisture content 17.72%, the drying rate of 4.72%, energy consumed 55.97 MJ/kg, thermal efficiency 20,90% and drying efficiency of 4.83%. While the test results with an air floe rate of 6.97 m3/m shows better results with an average temperature of 68.13°C drying copra final moisture content 16.05%, the drying rate of 5.1%, energy consumed 32.47 MJ/kg, thermal efficiency 55.57% and drying efficiency of 8,25%..AbstrakPanas buang PLTU memiliki potensi energi yang cukup tinggi yang dapat dimanfaatkan kembali untuk berbagai proses, salah satunya untuk pengeringan bahan. Tujuan dari penelitian ini adalah untuk mengetahui unjuk kerja alat pengering dengan memanfaatkan panas buang dari PLTU berbahan bakararang tempurung kelapa yang telah dikembangkan oleh P3TKEBTKE. Alat pengering tipe rak yang terdiri dari komponen kipas, heat exchanger, dan ruang pengering dipasang pada saluran gas buang pembakaran boiler sebagai sumber panasnya. Pada penelitian ini dilakukan pengujian dengan variasi laju alir udara4.14 m3/m dan 6.97 m3/m. Hasil pengujian dengan laju alir udara 4,14 m3/m menunjukkan rata-rata suhu pengeringan 72.18°C kadar air kopra akhir 17.72%, laju pengeringan 4.72%, kebutuhan energi untuk menguapkan air dari produk kopra adalah 55.97 MJ/kg, efisiensi termal pengering 20.90%, dan efisiensi sistem pengeringan 4.83%. Sedangkan hasil pengujian dengan kecepatan 3.7 m/s menunjukkan hasil lebih baik dengan rata-rata suhu pengeringan 68.13°C kadar air kopra akhir 16.05%, laju pengeringan 5.1%, kebutuhan energi untuk menguapkan air dari produk kopra adalah 32.47 MJ/kg, efisiensi termal pengering 55.57%, dan efisiensi sistem pengeringan 8.25%.